The Biological Standard of Living in Zurich during WWI - Joël Floris; Consuela Müller; Ulrich Woitek (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The paper analyzes the class specific biological standard of living in the city of Zurich during World War I. We find an increase of aver- age human stature for lower class conscripts born during this period, while the average height of conscripts from the upper and middle class stagnated or even decreased, despite the lack of change in the income differential. A potential explanation of this phenomenon could be the changes in access to food and consumption habits, affecting terminal height via changes in milk consumption.
Keywords: N34; N94; I30; 330